Exploratory study of sport-related concussion effects on peripheral micro-RNA expression. (21st March 2019) - Svingos, Adrian M.; Asken, Breton M.; Bauer, Russell M.; DeKosky, Steven T.; Hromas, Gabrielle A.; Jaffee, Michael S.; Hayes, Ronald L.; Clugston, James R.
ABSTRACT: Objective : Explore changes in micro-RNA (miRNA) expression in blood after sport-related concussion (SRC) in collegiate athletes. Methods : Twenty-seven collegiate athletes ( 41% male, 75% white, age 18.8 ± 0.8 years) provided both baseline and post-SRC blood samples. Serum was analyzed for expression of miR-153-3p (n = 27), miR-223-3p (n = 23), miR-26a-5p (n = 26), miR-423-3p (n = 23), and miR-let-7a-5p (n = 23) at both time points via quantitative polymerase chain reaction (qPCR). Nonparametric analyses were used to compare miRNA expression changes between baseline and SRC and to evaluate associations with clinical outcomes (symptom severity, cognition, balance, and oculomotor function, and clinical recovery time). Results : Participants manifested a significant increase in miRNA expression following SRC for miR153-3p (Z = −2.180, p = .029, 59% of the participants increased post-SRC), miR223-3p (Z = −1.998, p = .046, 70% increased), and miR-let-7a-5p (Z = −2.190, p = .029, 65% increased). There were no statistically significant associations between changes in miRNA expression and clinical test scores, acute symptom severity, or clinical recovery time. Conclusion : MiR-153-3p, miR-223-3p, and miR-let-7a-5p were significantly upregulated acutely following SRC in male and female collegiate athletes compared to baseline levels, though several athletes demonstrated no change or a decrease in expression. The biological mechanisms and functional implications of the increased expression of these circulating miRNA are unclear and require more research, as does their relevance to clinical outcomes.